If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) = -3(x + 7) + -1 Reorder the terms: 2(4 + x) = -3(x + 7) + -1 (4 * 2 + x * 2) = -3(x + 7) + -1 (8 + 2x) = -3(x + 7) + -1 Reorder the terms: 8 + 2x = -3(7 + x) + -1 8 + 2x = (7 * -3 + x * -3) + -1 8 + 2x = (-21 + -3x) + -1 Reorder the terms: 8 + 2x = -21 + -1 + -3x Combine like terms: -21 + -1 = -22 8 + 2x = -22 + -3x Solving 8 + 2x = -22 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 8 + 2x + 3x = -22 + -3x + 3x Combine like terms: 2x + 3x = 5x 8 + 5x = -22 + -3x + 3x Combine like terms: -3x + 3x = 0 8 + 5x = -22 + 0 8 + 5x = -22 Add '-8' to each side of the equation. 8 + -8 + 5x = -22 + -8 Combine like terms: 8 + -8 = 0 0 + 5x = -22 + -8 5x = -22 + -8 Combine like terms: -22 + -8 = -30 5x = -30 Divide each side by '5'. x = -6 Simplifying x = -6
| -9p-3(2-5p)=4(p-3)-12 | | (2x-4)=22 | | 7b+8=1064 | | c(260)=.3(260)+50 | | 96-4x=14x+18 | | 5k-10=56 | | 6m+4-3m=7(m-2)-2 | | 3x-4(10)= | | x+9=y | | 2x^2-3x-464=0 | | -5-15-25= | | 20=-5(x-7) | | 128=4(7x+4) | | (1-3x)(x-1)= | | -8x-(x+6)=4-x | | 3(3x-1)+5x=5(5+x) | | -2y-3y+8=-5y-12 | | 9-9x=87-3x | | 5(2x+3)=4(3x+2)-3 | | 5x-2=4(x+1) | | 4(x-6)=6(x+2) | | 5(x+5)+9= | | 23x+-8+-14x=10 | | 2x+14=5x-8 | | n-4n-22=7n | | x(3+5)=7x-3 | | 2(x-4)+2x=32 | | 112-2x=5x-7 | | 2x-3-8x=-27 | | 1-3x(x-1)= | | 8x-7=9x+12 | | -147=-3+8a |